Synthesis, growth, structural, optical, thermal and mechanical properties of an organic Urea maleic acid single crystals for nonlinear optical applications. (July 2016) - Vinothkumar, P.; Kumar, R. Mohan; Jayavel, R.; Bhaskaran, A.
Abstract: A potential organic urea maleic acid (UMA) was synthesized and single crystals were grown at room temperature by slow evaporation and seed rotation methods. The grown crystal has been subjected to single crystal XRD analysis and found to have been crystallized in a noncentrosymmetric monoclinic crystal system with Cc as space group. The High resolution X-ray diffraction analysis revealed that the specimen is free from structural grain boundaries. The transparency of the grown crystal was confirmed by optical absorption and transmittance spectra with lower cut-off wavelength of 285 nm. The microhardness test was carried out on different planes to study the load dependent hardness values. The dislocation density of the UMA crystal was estimated from the etching studies. The dielectric permittivity and dielectric loss of the grown crystal was carried out as a function of frequency for different temperatures along three crystallographic axes. Thermal properties of UMA crystals were studied by TG-DTA analysis and it is stable upto 112 °C. The laser induced surface damage threshold of the grown crystal was measured using Nd: YAG laser. The birefringence of the crystal measured in the visible region was found to vary with the wavelength. The particle size dependent SHG of the sample was measured with different input energies by Kurtz's powder method using Nd:YAG laser. Highlights: Urea maleic acid crystal has been grown by slow evaporation and seed rotation methods. SHG efficiency of UMA was found to be 3.9 times that of KDP and close to urea. Birefringence values of UMA were measured as a function of wavelength. Laser damage threshold value of UMA was determined using Nd: YAG laser.